Inclusive Rehabilitation Tourism as an Effective Tool for Social Adaptation of Victims of the Russian Aggression in Ukraine - Володимир Антоненко (Ресторанний і готельний консалтинг: Інновації, 2025)
Topicality. As a consequence of russian military invasion of Ukraine, there is a growing number of people with disabilities. These include combatants and civilians who have suffered from bombings, shelling and other injuries caused by military actions. The aim of the article is to review the problems, features and prospects for the development of various directions in tourism for people with disabilities during the period of martial law and after the cessation of the russian-Ukrainian war. This research identifies the positive influence of inclusive rehabilitation tourism for people with disabilities. In the current socio-economic conditions of development and in the context of the country’s post-war state, inclusive rehabilitation tourism serves as a means of rehabilitation and recovery, learning and leisure organisation. Research methods. Theoretical analysis, comparative analysis, economic modeling, as well as marketing research methods, including surveys and mathematical processing of the obtained data are applied in this study. Results. Inclusive rehabilitation tourism is viewed as a modern type of tourism, the essence of which lies in ensuring the implementation of tourism activities by any person (regardless of their physical abilities) and accessibility to tourist locations. The role of social entrepreneurship is defined as an instrument for the development of inclusive and inclusive rehabilitation tourism in the context of Ukraine’s post-war recovery. Promising directions for the development of inclusive rehabilitation tourism for people with limited physical abilities are determined. The provision of tourist services to people with disabilities should take into account numerous specific peculiarities of their interaction with the environment.